Novel markers in predicting non-alcoholic liver fatty and metabolic syndrome in obese children and adolescents: Atherogenic index of plasma and monocyte / high-density lipoprotein cholesterol ratio - Haspolat, Yusuf; Unal, Edip (Journal of Surgery and Medicine, 2020)
Aim: The aim of this study is to investigate the relationship between metabolic syndrome (MetS), insulin resistance, waist circumference (WC) and non-alcoholic fatty liver disease (NAFLD) with atherogenic index of plasma (AIP) and monocyte/ high-density lipoprotein cholesterol ratio (MHR) among obese children and adolescents. Methods: The cross-sectional study consisted of 172 obese and 63 healthy children. Anthropometric and biochemical parameters [Weight, height and BMI SDS, WC, Complete blood count, aspartate-aminotransferase (AST), alanine-aminotransferase (ALT), insulin, glucose, total cholesterol (TC), high-density lipoprotein (HDL-C), triglyceride (TG) and low-density lipoprotein (LDL-C), homeostasis model assessment-insulin resistance (HOMA-IR), AIP, MHR] were assessed. The AIP was classified into three groups: Low (<0.11), intermediate (0.11–0.21) and high (>0.21) risk. The MetS definition proposed by the International Diabetes Federation was adopted. Results: BMI SDS, WC, HOMA-IR, TC, TG, LDL-C, AST, ALT, AIP, and MHR parameters were significantly higher among the obesity group (P<0.05 for each). The MetS was analyzed in 146 obese children older than 10 years of age and found positive in 49 (33.6%) children. The mean AIP and median MHR were significantly higher in the group with MetS than in the group without (P<0.001, P=0.017, respectively). A significant positive correlation was determined between AIP and WC, HOMA-IR, TG, ALT, MHR, and steatosis degree (r=0.34, P<0.001, r=0.289, P<0.001, r=0.863, P<0.001, r=0.292 P<0.001, r=0.447, P<0.001, r=0.298, P<0.001 respectively). Conclusion: Both AIP and MHR are simple, cheap, and easily calculable parameters. The AIP might be used as an effective marker to predict MetS, abdominal obesity, NAFLD and IR in obese children. In addition, the high MHR in obese children may be associated with an increased risk of cardiovascular disease and MetS.